On the Criminal Regulation of Critical Information Infrastructure from the Perspective of International Law - Lixin Zhu; Ruolin Zhang; Yue Ma (Washington University Global Studies Law Review, 2021)
Critical Information Infrastructure (CII) is the basic layer of the Internet, and its safe and continuous operation is the basis of network security. In recent years, crimes against critical information infrastructure have become more frequent and present a trend of transnational attacks. International cooperation to protect critical information infrastructure and jointly manage cyberspace crimes has become the best way to solve this international problem. In this governance process, international law principles, norms or maxims that have been widely recognized or formed should be respected. They are also the basic platform for cooperation and construction of governance models. International law principles such as the Charter of the United Nations, the Five Principles of Peaceful Coexistence, and other international legal norms also provide ideas and a basic normative framework for network governance. Therefore, the best choice to solve the problem is to construct a win-win network security global community of common destiny, and to regulate the crime of Critical Information Infrastructure from the perspective of international law.